An investigation into how value is created through water sensitive urban design - Mallett, Gregory David (Department of Construction Economics and Management, 2018)
A key challenge facing developing countries is the rapid increases in urbanisation and the effect this has on their water systems. Water sensitive urban design (WSUD) is a process that considers the entire water system with the aim of achieving a water sensitive city (WSC). However, little is known about how value can be created through WSUD in terms of the sustainability of urban precincts in South Africa. The researcher therefore considered the well-established literature highlighting the relationship between WSUD and sustainable urban development. To understand the value derived from these concepts, two case studies were assessed, namely the Victoria & Alfred Waterfront (V&A Waterfront) and Century City. However, it should be highlighted that due to the uniqueness of these cases, no generalisations from the findings can be generated. The methodology implemented for the case studies was social constructivist in nature and to satisfy the research objectives, semi-structured interviews were conducted, documentary material was gathered, and photographic evidence was collected. Moreover, a diverse collection of data was assessed, which was extracted through various methods of data collection, thereby resulting in an in-depth understanding of the case studies. This research concludes there is a relationship between WSUD, sustainable urban development and value. It further argues that the underlying principles of facilities management (FM) and more specifically urban FM provide a managerial framework that can connect these concepts to achieve sustainability for urban precincts. Furthermore, the study uncovered the need for value capture mechanisms as a form of infrastructure financing and value creation for urban precincts. However, it was established that neither case study make use of such mechanisms, so future research is required in this regard.